Optimal design of monopile offshore wind turbine structures using CBO, ECBO, and VPS algorithms - Kaveh, A; Sabeti, S (Scientia Iranica, 2019)
Considering both size and dimensions of the offshore wind turbine structures, design optimization of such structures is a fruitful yet, simultaneously, onerous task due to the tempestuous complexity of the problem, which mostly comes from their environment. However, in this study, a computerized methodology based on meta-heuristic algorithms, consisting of the Colliding Bodies Optimization (CBO), Enhanced Colliding Bodies Optimization (ECBO), and Vibrating Particle System (VPS), is presented such that more economic upshots can be accomplished. Hence, minimization of the total weight of the structure subjected to a number of structural constraints, including a frequency constraint, by applying the abovementioned algorithms is the underlying goal of this study. Using the data from Horns Rev I offshore wind farm, which is located in the coastlines of Denmark in the North Sea, this study is performed based on a simplified structural model of a monopile offshore wind turbine structure, which can be utilized in preliminary stages of pertinent projects for conducting suitable comparisons.